Zoneamento geoambiental aplicado ao planejamento da gestão ambiental e territorial do município de Colorado D'Oeste, RO - Melo Lisboa, Antônio de; Ferreira, Gilda Carneiro [UNESP] (My University, 2011)
This research is based on the physical characterization of the environment to support definition of the best land use for the county of Colorado D'Oeste, in State of Rondônia, Brazil. Remote sensing and geoprocessing techniques were applied to support the preparation of a Geoenvironmental Zoning, which was used to define strategies of territorial and environmental management in that county. Digital and analogical remote sensing products, acquired by satellites, and additional cartographic and thematic maps allowed a morphostructural analysis to define low and high structural associated study site tectonic. Subsequently, this information was used to support analysis of the physiographic compartmentation of the study area. Based on this study information, it is possible to define geoenvironmental subzones and local hidrological regime, soils, mineral components, texture, color, and sedimentary materials. By integrating previous described information, a synthesis cartographic map generated. Accordingly, this Cartographic Sheet spatially defined the best land use over the study area, indicates zones for conservation, agricultural, and regeneration (areas that should be recovered). Finally, the results of this research can contribute and support governmental and non-governmental organization and local communities could improve land use and soil management, avoiding natural resource destruction and future land scarcity in the county of Colorado D'Oeste.

Para ordenar o uso territorial do município de Colorado D’Oeste - RO, este trabalho fundamentou-se na caracterização do meio físico. Para tanto, foram utilizadas técnicas de Sensoriamento Remoto e Geoprocessamento, que possibilitaram a elaboração do Zoneamento Geoambiental, no intuito de contribuir para o fortalecimento da gestão territorial e ambiental daquele município. O uso de produtos de sensoriamento remoto, obtidos por satélites, acrescidos aos mapas bases do meio físico, permitiu a realização de estudos morfoestruturais que possibilitaram a definição de altos e baixos estruturais que associados à tectônica proporcionaram a compartimentação fisiográfica da área em questão. Com base em tais informações foi possível elaborar o mapa das subzonas geoambientais e caracterizá-las quanto ao regime hídrico, pedologia, constituições mineralógicas, textura, cor e materiais sedimentares presentes na mesma. A partir da integração destas informações foi gerada a carta síntese, contendo a espacialização de áreas destinadas ao uso, de áreas a serem preservadas e aquelas que devem ser submetidas a processos de recuperação. As informações geradas neste trabalho visam subsidiar as tomadas de decisão das instituições públicas, organizações não governamentais e comunidades locais, no que diz respeito ao ordenamento do uso do solo, sem acarretar a escassez da oferta dos recursos naturais existente no município de Colorado D’Oeste. Palavras-chave: Zoneamento Geoambiental, Fisiografia, Sensoriamento Remoto.
Geoambiental zoning applied to the planning of the environmental and territorial administration of the county of Colorado D'Oeste, RO
Keywords: Geoenvironmental zoning; Physiographic; Remote sensing; administration; agricultural management; cartography; environmental management; land use planning; mineral; natural resource; remote sensing; research work; soil management; tectonics; territory; thematic mapping; zoning; Colorado; United States